Culturally Responsive Project-Based Stem Learning in Rural Schools: Effects on Belonging, Critical Thinking, and Local Problem-Solving - Sarah Jenkins (Educational Innovation and Learning Transformation, 2026)
Rural schools are often represented through deficit narratives of limited resources, geographic isolation, and restricted access to advanced STEM opportunities. Although these barriers are real, rural communities also possess powerful assets for STEM learning, including local ecological knowledge, agricultural practices, water systems, small enterprises, land-based livelihoods, and intergenerational community expertise. This article develops and illustrates a culturally responsive project-based STEM learning model for rural secondary schools. The model connects disciplinary STEM standards with local problems such as water quality, soil health, waste management, crop resilience, renewable energy, and community infrastructure. Using a mixed-methods quasi-experimental model, the simulated study involved 612 students in Grades 7 to 9 across eight rural schools, with four schools implementing a twelve-week culturally responsive PBL STEM unit and four comparison schools continuing standard STEM instruction. Published evidence supports the model's plausibility: Chen and Yang's project-based learning meta-analysis reported an overall weighted effect size of d = 0.71 for academic achievement across 46 comparisons, while Dee and Penner found that culturally relevant ethnic studies increased attendance by 21 percentage points and GPA by 1.4 grade points in a causal study. The simulated intervention results show stronger gains in STEM achievement, critical thinking, belonging, and locally grounded problem-solving. The article argues that rural STEM transformation requires moving beyond access-to-STEM narratives toward asset-based, culturally responsive, community-connected learning.